A Historical Approach of Change in Management Accounting Topics Published in Romania - Madalina Dumitru; Daniela Artemisa Calu; Catalina Gorgan; Adriana Calu (Journal of Accounting and Management Information Systems (JAMIS), 2011)
The change in management accounting is a topical issue in international research in management accounting. We analysed the change in the management accounting from an international perspective. We also want to see which the situation in Romania is. In order to analyse it, we studied the articles published in management accounting in Romania since 1908 in top journals. We considered four time ranges established on historical and academic changes. In the final section of the paper we presented a few directions to be considered for the future research in management accounting in Romania. The conclusion was that from 1990 until 2004 the articles presented modern cost calculation methods and the trends identified in other countries. After 2005 the research topics in the Romanian journals were traditional as compared with the research topics in MAR.
Keywords: M41; 650; Management accounting; change; economic journals; evolution; history